Visible-light induced dearomatization reactions - Cheng, Yuan-Zheng; Feng, Zuolijun; Zhang, Xiao; You, Shu-Li (Chemical Society reviews, 2022)
Dearomatization reactions provide rapid access to structurally complex three-dimensional molecules from simple aromatic compounds. Plenty of reports have demonstrated their utilities in the synthesis of natural products, medicinal chemistry, and materials science in the last decades. Recently, visible-light mediated photocatalysis has emerged as a powerful tool to promote many kinds of transformations. The dearomatization reactions induced by visible-light have also made significant progress during the past several years. This review provides an overview of visible-light induced dearomatization reactions classified based on the manner in which aromaticity is disrupted. This review provides an overview of visible-light induced dearomatization reactions classified based on the manner in which aromaticity is disrupted.